PEMIKIRAN PSIKOLOGI ISLAM DALAM IMPLIKASI PENDIDIKAN SOSIAL - ADNAN ADNAN (fakultas Ushuluddin dan Dakwah IAIN Bone, 2020)
Abstract Development of psychological thought in the contemporary Islamic world background by Islamization movement science and technology. This wave is sweeping across the region, including Indonesia Muslims. Particularly in Indonesia, recent decades among Indonesian Muslim psychologists appear on the psychology of Islamic discourse. The emergence of Islamic discourse psychology can be viewed from two sides. On the one hand, this is an indication of the influence of the waves and the spirit of Islamization of science and technology that have started to emerge since the 1980s. On the other hand, is a reflection of the consciousness of most Indonesian Muslim psychologists are beginning to understand the limitations of psychology in explaining the reality of human existence in the plenary. Enthusiasm for the emergence of Islamic Psychology encourages the implementation of various symposia, seminars, and publishing a book on the psychology of Islam. But this movement is still periferial, although it should be recognized that these discourses have led to fundamental problems, or in other words, some psychologists Muslim Indonesia began in earnest to realize the limitations of psychological theories that have been established in expressing real human existence. Thus the need to conduct a study of alternatives in discussing human. To realize this, of course not impossible though not without obstacles. Some of the main inhibiting factor is the attitude of Muslim psychologists are not uniform, namely: apathy, fanatical, secularists, and idealistic antagonist. Other inhibiting factors are partially psychologist Muslim fascination with theories that have been established and developed that does not come from Islam. Keywords: Psychological of Islamic, social-education